Inner detached frequency response curves: an experimental study - Gatti, Gianluca; Brennan, Michael J. (Journal of sound and vibration, 2017)
Certain nonlinear vibrating systems have frequency response curves (FRCs), in which isolated detached curves exist inside the main continuous FRC. The behavior of these systems has hitherto been studied analytically and numerically, but to the authors’ knowledge, there is no record of an inner detached FRC being detected experimentally. These curves may be hidden by numerical or experimental analysis, particularly when a system is subject to swept or stepped-sine excitation. Their existence may thus lead to unexpected dramatic changes in the amplitude of the system response. This paper presents an experimental study that involves the design, construction and testing of a specific system that has an isolated detached FRC inside the main continuous FRC. The experimental design of the test rig is supported by multibody dynamic simulations, and in the experimental tests the existence of a detached FRC was verified.